Use of the TPI and TWI Methods for Identifying Karst Dolines in Purwosari District, Gunungkidul Regency, Indonesia - Astrid Damayanti; Muhammad Fauzan Akmal Hidayat; Riza Putera Syamsuddin; Diko Hary Adhanto (Forum Geografi, 2025)
Gunung Sewu Karst, located in the Gunung Kidul Regency within the Special Region of Yogyakarta, features a distinctive karst topography consisting of dolines, hills and caves. Despite its aesthetic appearance, the area often experiences water scarcity due to the lack of surface water. Dolines, basin-like depressions formed during the karstification process, play a crucial role in biodiversity conservation, ecology, hydrology and land-use management planning. This study aims to map and identify the spatial distribution and morphometric characteristics of dolines in the Purwosari subdistrict, which have important implications for water resource management and drought mitigation in karst regions. The findings are intended to guide spatial planning and environmental mitigation strategies. Data for the study were derived from a digital elevation model (DEM), more scalable and accessible elevation data, to generate the Topographic Position Index (TPI) and Topographic Wetness Index for analysing doline spatial patterns, their terrain shapes, their types (dry or watery), and morphometry. The results show that dolines are associated with negative TPI values (58%) and low TWI values (53.48%), with most landforms classified below the plain level (27.91%). A significant proportion of dolines (79.06%) contain water, with the classification accuracy between TPI and TWI being 65.11%. Morphologically, most dolines are U-shaped, with oval-shaped dolines being the most common (41.86% of observations). The findings reveal that dolines in the Purwosari Subdistrict have significant underground water storage potential, making them crucial for mitigating regional drought risks.